Influence Of Resource Mobilization On Competiveness Of Tvet Institutions In Kenya - Gachunga, Monica Njeri (Machakos University Press, 2021)
The aim of this paper is to assess the influence of resource mobilization on competitiveness of TEVT institutions in Kenya. TVET institutions have been facing tremendous challenges, despite their immense contribution in the country’s education sector and to the economy at large. The institutions have been characterized with low intakes and their level of competitiveness has been shrinking over the years. One of the key lacking aspects among the institutions has been inadequacy in resources including finances, human resource and infrastructure. This has seen most of the TVET colleges struggle to meet their daily operational needs thus incapacitating them to remain effective. Despite the evidence of lack of resources in the TVET colleges, there have scant evidence on the efforts by the institutions to mobilize these resources for continued performance. It is against this background that this study seeks to assess the ability of the leaders in the TVET institutions to mobilize the resources and how these resources affect competitiveness of the institutions. This study was informed by the resource dependency theory. A descriptive research design was employed while the target population was TVET institutions in Kenya. A total of 272 respondents were purposively sampled from the 68 TVET institutions in Kenya. A structured questionnaire was used to collect data which was analysed using SPSS. The findings revealed that resource mobilization was an integral aspect of strategic leadership that steered the competitiveness of the TVET institutions in Kenya. The study concluded that TVET institutions lacked adequate resources which could enhance their competitiveness thus recommending the need for leaders in these institutions to develop ways through which adequate resources can be mobilized.
Keywords: Resource Mobilization; Strategic Leadership; TVET institutions; Institutional competitiveness